Language learner strategies thirty years of research and practice (Oxford applied linguistics, 2007)
Research into language learner strategies has the fundamental goal of improving the teaching and learning of second languages. This book explores the notion that the reason some learners of second languages excel and others struggle lies in what the learners themselves do-the strategies they bring to language learning and to language use. Name of series: Oxford Applied Linguistics.